VD_FINDINFO AM 19/18 - 28/2018 vom 6. Juni 2018 - VD Tribunal cantonal (2018)
REMBOURSEMENT DE FRAISASSURANCE, ASSURANCE OBLIGATOIRE, FRAIS DE MÉDICAMENTS | 190 Cst., 30 Cst., 5 al. 3 Cst., 9 Cst., 24 LAMal, 25 LAMal, 32 al. 1 LAMal, 34 al. 2 LAMal, 36 OAMal